Pan-Cancer Analyses Reveal Oncogenic and Immunological Role of Dickkopf-1 (DKK1) - Gao, Shuang; Jin, Ye; Zhang, Hongmei (Frontiers in Genetics, 2021)
WNT signaling pathway inhibitor Dickkopf-1 (DKK1) is related to cancer progression; however, its diagnostic and prognostic potential have not been investigated in a pan-cancer perspective. In this study, multiple bioinformatic analyses were conducted to evaluate therapeutic value of DKK1 in human cancers. The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) were served as data resources. Wilcoxon rank test was performed to evaluate the expression difference of the DKK1 between cancer tissues and normal tissues. Kaplan-Meier curve and cox regression were used for prognosis evaluation. Single sample gene set enrichment analysis (ssGSEA) was used to evaluate the association of DKK1 expression with the immune cell infiltration. The potential function of DKK1 was explored by STRING and clusterProfiler. We found that the expression level of DKK1 is significantly different in different cancer type. Importantly, we demonstrated that DKK1 is an independent risk factor in ESCA, LUAD, MESO and STAD. Further analysis revealed that DKK1 had a large effect on the immune cell infiltration and markers of certain immune cells, such as Th1 and Th2 cells. PPI network analysis and further pathway enrichment analysis indicated that DKK1 was mainly involved in WNT signaling pathway. Our findings suggested that DKK1 might serve as a marker of prognosis for certain cancer by affecting on WNT signaling pathway and tumor immune microenvironment.